The impact of postponing 2020 Tokyo Olympics on the happiness of O-MO-TE-NA-SHI workers in tourism: A consequence of COVID-19 - Yamamura, E.; Tsutsui, Y. (Sustainability, 2020)
The 2020 Tokyo Olympics has been postponed due to the novel coronavirus (COVID-19) pandemic. The implications for industries related to the Olympics—tourism, hotels and restaurants, and others—are expected to be affected by reduced demand. Japanese workers in these industries were prepared to offer their hospitality to visitors from around the world. They would be satisfied from not only an increase in income but also in offering visitors a taste of Tokyo`s great hospitality if the Olympics had been held in 2020. However, postponement of the sporting event is likely to have a significant impact on their happiness level. We independently collected individual-level panel data from March to April 2020. Based on this, we found that the happiness level of workers in the tourism and restaurant sectors declined drastically after the announcement of the postponement. Only two weeks later, their happiness level did not alter from the pre-announcement level. This tendency was strongly observed in Tokyo and the surrounding prefectures, but not in other prefectures. However, workers engaged in the tourism and restaurant sectors did not predict a decrease in their income even after the postponement. Combined, these findings indicate that loss of extending hospitality, rather than reduction in income, temporarily reduces the happiness level of workers.